Analisis Peran Kepala Sekolah dalam Meningkatkan Manajemen Mutu Sekolah di Mi Darul Hikam Kota Batu - Ariesta, Eliza; Hananuraga, Rahula (ALACRITY : Journal of Education, 2024)
This study aims to analyze the role of school principals in enhancing school quality management at MI Darul Hikam in Batu City. The research method employed is qualitative with a case study approach. Data are collected through in-depth interviews, observations, and documentary studies. Research respondents include school principals, teachers, staff, and parents of students. Data analysis is conducted using descriptive and qualitative analysis techniques. The results show that the role of the school principal is highly significant in enhancing school quality management. The school principal serves as a visionary leader, facilitator, motivator, and key driver in implementing various school quality improvement programs. Good support and communication from the school principal strengthen coordination among staff and teachers in achieving common goals. Furthermore, the school principal also plays a role in motivating teachers and staff to innovate and improve their performance.